Indonesian Natural Materials for Sustainable Ocean Structures: Synergizing Nibung Wood Characterization, Fiber Composites, and Processing Innovations - Sitorus, Bintang Natan; Hermanto, Mochammad Fathurridho; Nandalianadhira, Nafisa (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
This research explores the potential of Indonesian natural materials - specifically Nibung wood (Oncosperma tigillarium) and vegetable fibers (jute, ironwood) - for sustainable ocean structures. The literature review focused on: (1) mechanical and physical characterization of Nibung wood; (2) optimization of Nibung-fiber thermoplastic composites using the Taguchi-GRA method; (3) evaluation of jute fiber resistance to seawater uptake; and (4) innovation of traditional Bajau modular connection techniques. The narrative-thematic method categorizes the findings based on material characteristics, surface modification, structural performance, and marine tidal applications. Results showed Nibung wood has strength class II-III (density 0.53 g/cm³; MOE 5,848 MPa; MOR 4,325 MPa), optimized Nibung-rPP WPC (<2% water absorption, tensile strength >30 MPa), and jute fibers experienced ≤10% impact reduction after 84 days of sea immersion. Bajau- style modular joint detailing improved airflow and minimized moisture accumulation. Recommendations include integration of Nibung wood in local thermoplastic WPC, alkali-coupling treatment, and adaptation of modular joints for modern oceanstructures.